Improving Students’ Numeracy and Literacy Skills Through a Contextual Approach - Huda, Nuril (PT. Anagata Sembagi Education, 2025)
Numeracy literacy skills are one of the essential competencies of the 21st century, yet national and international assessments show that elementary school students in Indonesia still face difficulties in connecting mathematical concepts to real-world contexts. This study aims to evaluate the effectiveness of a contextual-based numeracy literacy learning model combined with simple digital media in improving student achievement. The research method used a quasi-experimental design with a pretest–posttest control group model. Two classes were designated as the experimental and control groups, with an intervention of eight meetings based on everyday life contexts (e.g., market prices and rainfall data) combined with simple digital media such as spreadsheets and visual simulations. The results of the ANCOVA analysis showed a significant difference between the experimental and control groups, with a large effect size (Hedges' g = 1.12). The strongest improvement occurred in the formulate aspect, followed by employ and interpret. Qualitative findings through interviews and observations also showed increased motivation, active participation, and self-confidence in students. Thus, the contextual model with simple digital support is effective in improving numeracy literacy and is relevant for wider implementation as a learning strategy, while supporting the achievement of SDG 4 on quality and inclusive education.